2004
DOI: 10.1590/s1415-47572004000300019
|View full text |Cite
|
Sign up to set email alerts
|

Mating system of a population of Myracrodruon urundeuva F.F. & M.F. Allemão using the fAFLP molecular marker

Abstract: The mating system and genetic diversity were studied in a natural population of Myracrodruon urundeuva originating from 30 open-pollinated trees at the Paulo de Faria Ecological Station, SP, Brazil. The progenies were planted on the Teaching and Research Farm of the Ilha Solteira Engineering School, UNESP. Using the fAFLP molecular marker, eleven loci were selected to study the mating system. The mating system was analyzed using the multilocus mixed-mating model. The estimates of genetic divergence between pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
11
1
1
Order By: Relevance
“…The outcrossing estimates obtained in the present study and by Degani et al (1997) indicate that mango is a predominantly open pollinated species and that biometrical models applied to mangoes should take into account the deviation from random outcrossing to estimate genetic parameters and the constitution of broad germplasm samples to preserve the genetic variability of the species, as recommended by Freitas et al (2004), while evaluating Myracrodruon urundeuva.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The outcrossing estimates obtained in the present study and by Degani et al (1997) indicate that mango is a predominantly open pollinated species and that biometrical models applied to mangoes should take into account the deviation from random outcrossing to estimate genetic parameters and the constitution of broad germplasm samples to preserve the genetic variability of the species, as recommended by Freitas et al (2004), while evaluating Myracrodruon urundeuva.…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, it is important to establish strategies for the effective conservation of any species. The mating system, together with the mechanism of pollen and seed dispersion, determines part of the genetic structure of populations (Freitas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, outcrossing rates have been traditionally studied using co-dominant markers such as isozymes and microsatellites due to their high allelic polymorphism (Chaix et al, 2003;Adugna et al, 2013;Sinha et al, 2015;Sharma et al, 2017). However, when microsatellite markers were unavailable, several dominant markers such as RAPD (Gjuric and Smith, 1996), ISSR (Ge and Sun, 1999;Han et al, 2009), and AFLP have been used to estimate outcrossing rates as they are able to produce very large numbers of informative loci without previous genetic information about the genetic system in plant species (Gaiotto et al, 1997;Freitas et al, 2004;Muluvi et al, 2004;Pometti et al, 2013;Sinha et al, 2015;Sharma et al, 2017 ). Amplified fragment length polymorphisms (AFLPs) are easily applied to new species, since DNA sequence knowledge is not required for this technique unlike co-dominant markers such as microsatellites (Vos et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A species can produce offspring through different types of mating, such as random outcrossing, correlated outcrossing, biparental inbreeding, self-pollination, apomixes or a combination of these reproductive strategies. Plant reproduction, together with the mechanisms of pollen and seed dispersal, determines the genetic structure of plant populations (Freitas et al 2004).The plant species that result from outcrossing maintain the majority of their distributed genetic variability within the population, in contrast to a predominantly self-pollinated species in which the majority of the genetic variability is distributed between populations (Hamrick & Godt 1989). Reproductive studies have revealed that a large number of plant species are allogamous or possess a mixed mating system that is predominantly allogamous (Gusson et al 2006).…”
mentioning
confidence: 99%
“…Therefore, biometrical models applied to this species should take into account deviation from random outcrossing to estimate genetic parameters. As recommended by Freitas et al (2004), while evaluating Myracrodruon urundeuva, biometrical models should also account for the constitution of broad germplasm samples to preserve the genetic variability of the species.The high heterozygosity levels observed in the analyzed umbu tree families were also an important variable for the in situ conservation of this species because new allelic recombination can occur, thus making it possible for the appearance of new genotypes that are readily adapted to environmental changes and for the colonization of new areas.More than 932 savanna-like plant species, including 380 endemic species, have been identified in the Brazilian semiarid Region (Brasil 2002). The majority of these species have not been studied or sampled to form a germplasm collection, which increases the risk of losing genetic variability of the adapted species to xerophytic conditions.…”
mentioning
confidence: 99%